64 Immunological, physiological, and behavioral responses to an experimentally-induced respiratory disease challenge in growing steers - Wottlin, Lauren (J Anim Sci, 2020)
Immunologic, physiologic, and behavioral responses to a combined viral-bacterial respiratory challenge were explored in beef steers (initial BW 293 kg). Steers (n = 24) were inoculated intranasally with bovine herpes virus-1 (2×10(8) PFU) and intratracheally with Mannheimia haemolytica (MH, 2.15×10(10) CFU) on days -3 and 0, respectively, (n = 16; VB), or similarly inoculated with phosphate-buffered saline (n = 8; PBS). Venous and arterial blood were collected on -3, -1, 0, 2, 3, 5, 7, 10, and 14 relative to MH challenge for CBC, haptoglobin, and arterial blood oxygen saturation analysis. Continuously recorded variables included rumen temperature, activity, rumination, DMI, and feeding behavior. Data were analyzed with a repeated-measures mixed model (SAS 9.4) with fixed effects of day, inoculation, and the interaction. Bunk visit frequency and DMI were reduced (P < 0.01) in VB steers throughout the 14 d post-MH period compared to PBS steers. Rumination (days 1, 7) and activity (days 1, 2, 4–8, and 11–13) were reduced (P < 0.03) in VB steers vs PBS steers. Rumen temperature was elevated (P < 0.04) in VB steers until day 6 post MH inoculation. Neutrophil concentrations (days 2 and 3), platelets (days 7–14), fibrinogen (days 2–10), and haptoglobin (days 2–7) were elevated (P < 0.05) in VB vs PBS steers. Hematocrit was depressed (P < 0.05) in VB steers on days 3–10. The VB steers had decreased (P < 0.05) arterial (S)O(2)% and pO(2) than PBS steers; however, the inoculation × day interaction was not significant. Results indicate that the experimental VB challenge substantially altered rumen temperature, DMI, feeding behavior, rumination and immunological response as expected. Arterial sO(2)% and pO(2) concentrations were reduced minimally by VB challenge, indicating challenges in using blood gas to detect BRD in beef cattle.